Different Definitions of Prevalent Hypertension Impact: The Clinical Epidemiology of Hypertension and Attainment of Healthy People Goals. Issue 3 (26th December 2012) - Egan, Brent M.; Zhao, Yumin
Abstract : Prevalent hypertension in National Health and Nutrition Examination Surveys (NHANES) is traditionally defined as blood pressure (BP) ≥140 mm Hg systolic and/or ≥90 diastolic and/or currently taking antihypertensive medications. When estimating prevalent hypertension, American Heart Association (AHA) statistical updates include the traditional definition of hypertension (tHTN) and untreated individuals with nonhypertensive BP told twice that they were hypertensive (nontraditional [ntHTN]). The characteristics of ntHTN and their impact on the clinical epidemiology of hypertension and Healthy People prevention and control goals are undefined. NHANES 1999–2002, 2003–2006, and 2007–2010 were analyzed. The ntHTN group was younger and had less diabetes and lower BP than the tHTN group but higher BP than the normotensive group. When classifying ntHTN as hypertensive, prevalent hypertension increased approximately 3% and control 5% to 6% across NHANES periods. In 2007–2010, the Healthy People 2010 goal of controlling BP in 50% of all hypertensive patientss was attained when ntHTN was classified as hypertension (56.5% [95% confidence interval (CI), 54.2–58.7]) and nonhypertension (51.8% [95% CI, 49.6–53.9]). When including ntHTN in prevalent hypertension estimates, the Healthy People 2020 goal of controlling BP in 60% of hypertensive patients becomes more attainable, whereas reducing prevalent hypertension to 26.9% (31.8% [95% CI, 30.5–33.1]) vs 28.7% [95% CI, 27.5–30.0]) becomes more challenging.